An Introduction to the Evolution of Single and Binary Stars - Benacquista, Matthew. (Undergraduate Lecture Notes in Physics,, 2013)
An Introduction to the Evolution of Single and Binary Stars provides physicists with an understanding of binary and single star evolution, beginning with a background and introduction of basic astronomical concepts. Although a general treatment of stellar structure and evolution is included, the text stresses the physical processes that lead to stellar mass compact object binaries that may be sources of observable gravitational radiation. Basic concepts of astronomy, stellar structure and atmospheres, single star evolution, binary systems and mass transfer, compact objects, and dynamical systems are covered in the text. Readers will understand the astrophysics behind the populations of compact object binary systems and have sufficient background to delve deeper into specific areas of interest. In addition, derivations of important concepts and worked examples are included. No previous knowledge of astronomy is assumed, although a familiarity with undergraduate quantum mechanics, classical mechanics, and thermodynamics is beneficial.